Evaluation of novel jointless engineered cementitious composite ultrathin whitetopping (ECC-UTW) overlay. (30th December 2020) - Hungria, Ricardo; Arce, Gabriel; Hassan, Marwa; Anderson, Michele; Mahdi, Moinul; Rupnow, Tyson; Bogus, Susan M.
Highlights: Two full-scale jointless ECC-UTW sections (101.6-mm and 63.5-mm thick, respectively) were constructed and monitored. Generally, mechanical properties of ECC manufactured on a large-scale underperformed those of ECC manufactured under laboratory conditions. Seven months post-construction, the 63.5-mm thick ECC-UTW presented microcracks attributed to normal functioning of ECCs' PSH mechanism. Yet, the 101.6-mm thick ECC-UTW exhibited macrocracks associated mainly with areas of heavy instrumentation and/or where fiber clumps occurred. Due to potential jointless functionality and thickness reduction, ECC-UTWs may present a cost-effective alternative to conventional concrete UTWs. Abstract: The objective of this study was to evaluate the construction, material characterization, initial structural assessment, and cost of a novel jointless Engineered Cementitious Composite Ultra-Thin Whitetopping (ECC-UTW) overlay. After construction, early-age cracks (from less than 0.25 mm to up to 2.54 mm width) were observed in the 101.6-mm (4 in.) jointless ECC-UTW section; yet, the majority of the cracks coincided with areas where fiber clumps were observed during construction and places of heavy instrumentation. On the other hand, no cracks were observed in the 63.5-mm (2.5 in.) jointless ECC-UTW at early ages; yet, when winter arrived, micro-cracks (<0.25 mm in width) developed. These micro-cracks were attributed to the normal functioning of the ductile pseudo strain-hardening (PSH) mechanism of ECC materials. Falling Weight Deflectometer (FWD) evaluation conducted before and after the construction of the UTWs showed a significant reduction in pavement deflection after construction. This deflection reduction was much more substantial for thicker 101.6-mm UTWs; yet, no major difference in deflection reduction was found between the 101.6-mm ECC and the 101.6-mm regular concrete UTW sections. The 28-day compressive and flexural strength of ECC evaluated from field specimens underperformed that of previous studies by 9.6% and 14.8%, respectively; however, deflection capacity slightly outperformed that of previous studies by 4.1%. The flexural performance of the ECC material was vastly superior to that of regular concrete exceeding the flexural strength by 92%. All specimens evaluated in uniaxial tension exhibited a PSH behavior after first-cracking; however, the tensile strength and tensile ductility values obtained underperformed expected values for ECC M3-15% and exhibited substantial variability. Uniaxial tensile test results from field specimens were deemed unreliable. Cost analysis results showed that a cost reduction of 14.8% per lane kilometer is expected by implementing the proposed jointless ECC-UTW system compared to that of the regular jointed concrete UTW. The greatest construction cost savings for utilizing ECC originates from its potential jointless attribute and its reduced thickness.